2003
DOI: 10.1121/1.1596173
|View full text |Cite
|
Sign up to set email alerts
|

The broadband social acoustic signaling behavior of spinner and spotted dolphins

Abstract: Efforts to study the social acoustic signaling behavior of delphinids have traditionally been restricted to audio-range (<20 kHz) analyses. To explore the occurrence of communication signals at ultrasonic frequencies, broadband recordings of whistles and burst pulses were obtained from two commonly studied species of delphinids, the Hawaiian spinner dolphin (Stenella longirostris) and the Atlantic spotted dolphin (Stenella frontalis). Signals were quantitatively analyzed to establish their full bandwidth, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(132 citation statements)
references
References 18 publications
6
119
1
6
Order By: Relevance
“…During feeding, part of the fi sh was tossed in the water to feed the mother and calf, a method which might have triggered a heightened production of clicks by the whales (Dreher, 1966;dos Santos and Almada, 2004) that used the fi sh as a target. Moreover, the fi sh tossed into the tank might have developed competition among the animals with an increase in production of burst pulses (Overstrom, 1983;Connor and Smolker, 1996;Herzing, 1996;Lammers et al, 2003;Nowacek, 2005). Moreover, Ridgway et al (2014) suggested that burst pulses produced during feeding sessions might be considered as food calls with emotional content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During feeding, part of the fi sh was tossed in the water to feed the mother and calf, a method which might have triggered a heightened production of clicks by the whales (Dreher, 1966;dos Santos and Almada, 2004) that used the fi sh as a target. Moreover, the fi sh tossed into the tank might have developed competition among the animals with an increase in production of burst pulses (Overstrom, 1983;Connor and Smolker, 1996;Herzing, 1996;Lammers et al, 2003;Nowacek, 2005). Moreover, Ridgway et al (2014) suggested that burst pulses produced during feeding sessions might be considered as food calls with emotional content.…”
Section: Discussionmentioning
confidence: 99%
“…The type of sounds produced by false killer whales are included either in the traditional categories such as whistles, clicks, and burst-pulses, or in the class of sounds with intermediate acoustic characteristics (graded sounds=click trains and whistles are at the opposite ends of a continuum) (Murray et al, 1998a, b) . It has been suggested that sounds with graded structure may communicate the animal's behavioral states, while acoustic emissions included in well-defi ned categories would indicate a unique function of the signals (Lammers et al, 2003: spotted dolphins, Stenella frontalis ; spinner dolphins, Stenella longirostris ; Herzing, 1996: spotted dolphins, Stenella frontalis ; Rehn et al, 2007, 2011Weir et al, 2007: sperm whales, Physeter macrocephalus ;Murray et al, 1998a, b: false killer whales, Pseudorca crassidens ). Even though diff erent studies have been performed on the characteristics of false killer whales' sounds (Busnel and Dziedzic, 1968;Kamminga and van Velden, 1987;Thomas et al, 1988;Au et al, 1995;Murray et al, 1998a, b;Rendell et al, 1999;Supin et al, 2003Supin et al, , 2004Supin et al, , 2005Madsen et al, 2004;Nachtigall and Supin, 2008), there is no information available on the eff ects of the controlled environment on the acoustic activity of this species of dolphin.…”
Section: Introductionmentioning
confidence: 99%
“…Masking impacts were modelled on the fundamental whistle contour because this has been shown to convey important information between animals (Janik et al 2006). It is possible that some species put more acoustic energy into the harmonics than in the fundamental contour (Lammers et al 2003), but it is unknown how information is distributed between the fundamental contour and the harmonics. Our assumption that noise masking narrow band signals is integrated by the auditory system over one-third octave bands roughly corresponds to the critical bandwidths found in bottlenose dolphins (Johnson 1968).…”
Section: Masking Impactsmentioning
confidence: 99%
“…The bottom is primarily sandy, with zones of rock, reef and patches of seagrass (Thalassia testudimum). The life history, including non-invasive genetic analysis, (Elliser & Herzing, 2012, 2013, 2016a, 2016bGreen, Herzing & Baldwin, 2007 and the development and use of social and acoustic behaviors of this community of Atlantic spotted dolphins have been documented extensively Herzing, 2000Herzing, , 2004Herzing, , 2005Herzing & Brunnick, 1997;Herzing & dos Santos, 2004;Herzing & Johnson, 1997;Herzing, Moewe & Brunnick, 2003;Lammers, Au & Herzing, 2003;Miles & Herzing, 2003;Welsh & Herzing, 2008).…”
Section: Methods Study Site Dolphin Community and Subjectsmentioning
confidence: 99%